2020
DOI: 10.1099/ijsem.0.004336
|View full text |Cite
|
Sign up to set email alerts
|

Mrakia stelviica sp. nov. and Mrakia montana sp. nov., two novel basidiomycetous yeast species isolated from cold environments

Abstract: Five yeast strains were isolated from soil and sediments collected from Alps and Apennines glaciers during sampling campaigns carried out in summer 2007 and 2017, respectively. Based on morphological and physiological tests and on phylogenetic analyses reconstructed with ITS and D1/D2 sequences, the five strains were considered to belong to two related but hitherto unknown species within the genus Mrakia, in an intermediate position between Mrakia cryoconiti and Mrakia arctica. The names Mrakia stelviica (holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The rest of the Mrakia clade assimilated maltose and melezitose, which suggests that those members might belong to M. gelida , M. blollopis or M. robertii (or M. stelviica in the example of isolate LP 2.1.2016): they were thus referred to as Mrakia sp. Turchetti et al (2020) emphasized the necessity of undertaking a more in-depth study of the Mrakia genera phylogeny along with the need for additional gene sequencing to achieve a correct identification of all of the known strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the Mrakia clade assimilated maltose and melezitose, which suggests that those members might belong to M. gelida , M. blollopis or M. robertii (or M. stelviica in the example of isolate LP 2.1.2016): they were thus referred to as Mrakia sp. Turchetti et al (2020) emphasized the necessity of undertaking a more in-depth study of the Mrakia genera phylogeny along with the need for additional gene sequencing to achieve a correct identification of all of the known strains.…”
Section: Discussionmentioning
confidence: 99%
“…Species of the Mrakia genus had been previously identified in Antarctic soil (Tsuji et al 2015, Martinez et al 2016). This genus seems to be adapted to cold environments, having been also isolated from Arctic environments, from Alpine and Apennine glaciers and from the cold forest in Abashiri, Japan (Nakagawa et al 2004, Thomas-Hall et al 2010, Tsuji et al 2018, Turchetti et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These species typically exhibit optimal growth temperatures ranging from 10-18°C, with upper limits not exceeding 20°C, indicating psychrophilic adaptations for thriving in consistently low temperatures. Additionally, five non-polar species from cold environments-such as lakes, glaciers, and cold soils-including M. aquatica, M. cryoconiti, M. montana, M. panshiensis, and M. steliica, also exhibit psychrophilic adaptations with maximum growth temperatures not exceeding 20°C [5,12,15]. In contrast, three non-polar species, M. fibulata from Germany and M. soli and M. terrae from Korea, exhibit optimal growth temperatures of about 15°C and maximum temperatures of about 25°C [14,16], suggesting psychrotolerant adaptations that enable survival in environments with more frequent temperature fluctuations.…”
Section: Ecologymentioning
confidence: 99%
“…We have previously isolated two basidiomycetous yeasts, M. hoshinonis, and V. ellesmerensis, from Walker Glacier and have described them as new fungal species [19,22]. Mrakia hoshinonis has also been isolated from the Calderone Glacier in Italy and Iceland [24], however no sequences with high homology (>95%) in the ITS region with V. ellesmerensis has been registered to date in GenBank. These results suggested that M. hoshinonis may be widely distributed in the Arctic and alpine regions while V. ellesmerensis is more locally restricted and perhaps endemic to the LIA region.…”
Section: Figure 2 Dendrogram Based On Bray-curtis Dissimilarities Bet...mentioning
confidence: 99%